Avaliação farmacoeconômica e epidemiológica das terapias hipolipemiantes - Juliana Giannetti Duarte (2012)
Lipid disorders are a public health problem of great importance and the drug therapies for its control considered high cost. There are 12 drugs available to treat lipid disorders in the Pharmaceutical Assistance Specialized Division by the Brazilian Unified Health Care System. This dissertation is one evaluation pharmacoeconomic and epidemiological of the lipid-lowering therapies presented as two papers. The first paper is a systematic review that evaluates the efficacy of therapeutic measures for the control and treatment of dyslipidemias. The electronic databases PUBMED and LILACS were used to search for publications focusing on dyslipidemia in order to subsidize discussions about the treatment recommended by the Protocol of the Ministry of Health of Brazil and IV Brazilian Guidelines on Dyslipidemia and Atherosclerosis Prevention published by the Department of Atherosclerosis of Brazilian Society of Cardiology. These studies were reviewed by two independent reviewers with the participation of a third reviewer when there was no consensus in the evaluation. The analyses were carried out in four steps: identification and exclusion of duplicated studies, analysis of titles and abstracts, full text analysis and quality assessment of studies according to the Jadad scale modified. Twenty-two studies were included in this review and confirmed the recommendation for the use of statins in hypercholesterolemic patients and fibrates in hypertriglyceridemic patients. The second article describes the costs and the demographic and epidemiological profile of the patients with dyslipidemias treated by the Pharmaceutical Assistance Specialized Division in the period of 2003 to 2006 and identifies the characteristics related to the individual average monthly expenses on drugs for the treatment of dyslipidemias. The knowledge of the profile of the users, use of drugs and related expenses contribute to decision-making aimed at changing the history framework of dyslipidemias, preventing the occurrence of cardiovascular diseases, saving scarce resources and increasing the efficiency of public policies. In the historical cohort created from the National Base of Users of Pharmaceutical Assistance Specialized Division, 67.142 individuals were included and the variables of interest classified as demographic, epidemiological and economic. The results of descriptive and multivariate analyses indicated a high frequency of pure hypercholesterolemia in adult women and elderly residents in the Southeast, of higher use of simvastatin and atorvastatin and individual average monthly expenditure of approximately R$ 68,00. It was observed that increasing age led to lower spending, that male patients were more likely to have higher expenditure and that atorvastatin was the drug that most increased average individual monthly expenditures. The epidemiological profile was consistent with the literature and the individual average monthly spending was high considering the Brazilian average family income. Changes in lifestyle, access to more effective drugs and appropriate guidelines on drugs need to be emphasized in order to change this scenario.